Collision Diagram Analysis and Weighted Ranking of Accident-Prone Areas (Black Spots) on the Road Network of Padangsidimpuan City - Ahmad Rafii (International Journal of Natural Science Studies and Development (IJOSS), 2026)
Padangsidimpuan City records traffic accidents concentrated on several road segments, yet mitigation efforts have generally focused on identifying accident-prone locations without examining collision characteristics. This study aims to rank accident-prone areas (black spots) using a multi-criteria weighting method, analyze collision patterns through collision diagrams, identify dominant contributing factors, examine the relationship between road geometry, vehicle speed, and accident patterns, and formulate segment-specific countermeasures. A quantitative descriptive approach was employed using 2021 traffic accident records from the Padangsidimpuan Traffic Police together with field surveys of road geometry and spot speeds. Black-spot ranking was based on casualty severity, road function, road status, and material losses. The results identified Jenderal Sudirman Road as the highest-ranked black spot (score = 49), followed by H.T. Rizal Nurdin Road (47), Abdul Haris Nasution 1 Road (35), Raja Inal Siregar Road (31), and Imam Bonjol Road (30). Collision diagram analysis identified head-on collisions as the dominant crash pattern, with Jenderal Sudirman Road recording the highest proportion (5 of 9 crashes; 55.6%). Human factors, particularly excessive speed and driver negligence, were the dominant contributing factors, reinforced by inadequate road infrastructure, including the absence of speed-limit signs, black-spot warning signs, and median separation. The study recommends speed management measures, installation of warning signs and rumble strips, median or centerline improvements, and implementation of a School Safety Zone (ZoSS) on school-front road segments. These findings provide practical guidance for transportation agencies and road authorities in prioritizing data-driven road safety improvements.